Understanding Olympic Values and Physical Activity in the adult population of Chile and Argentina - Bacot, Alejandro (Πανεπιστήμιο Πελοποννήσου, 2022)
The thesis has the aim to compare and examine the level of understanding the Olympic Values in the adult population (18-65 years) in Chile (n=100) and Argentina (n=100). Argentina was recent host country of the youth Olympic Games, and Chile will be host of the Panamerican Games in 2023, so it was worth investigating what the level of understanding the Olympic Values. The survey method has been developed with the theory of Fair Play from Jim Parry and the application of the moral influence scale and Moral Competence Test MCT by George Lind. There was also carried out comparison of the level of physical activity among the two populations of adults with the use of a survey methods. With the results of the survey, and with the comparison between countries it is possible to know the level of understanding the Olympic Values in that population, the moral factors who influence in population and the physical activity statistics in those countries. The average level of moral competence of the examined Argentine adult population turned out to be higher their among similar adult population of Chile and no impact of Buenos Aires Youth Olympic games (2018) was noticed in case of Argentina. The most influential factor concerning the source of influence on the level of moral competences pointed by the two examined population of adults of Chile and Argentina appeared to be parents. In case of physical activity, the situation in both countries seems to be similar, the level of physical activity, although a little bit higher among the adults of Argentina was still insufficient in some age-related groups, while in Chile it was more diverse.
Keywords: Ολυμπισμός; Ολυμπιακό κίνημα; Ολυμπιακές αξίες; Ολυμπιακοί Αγώνες Νέων - Αργεντινή; Olympism; Olympic movement; Olympic values; Youth Olympic Games - Argentina; olympism; Olympic Values; Physical Activity; Moral Competence; Fair Play